An Empirical Model for Compression of Chopped Water Hyacinth III a Closed Cylindrical Die - Mathur, S M; Singh, Pratap (Annals of Arid Zone, 2016)
Bulk chopped samples of fresh water hyacinth (Eichhornia crassipes) were compressed in a closed cylindrical die at 10 levels of compression pressures and five levels of die-charges at a minimum compression speed of 1.66 x 10-3 m s-I on Houn’s Field Universal Testing Machine. The complete compression process was observed and relationships were developed among compression ratio, compression pressures and die-charge. A combined relationship was also developed among both the independent and dependent variables. The relationship between compression ratio and compression pressure was simple power law while it showed a linear trend with the die-charge. Statistical analysis showed significant difference in compression ratio with pressure level and die-charge. Maximum compression ratio was 17.52 for die-charge of 0.020 kg and minimum was 4.95 for die-charge of 0.040 kg, at a maximum compression pressure of 2.54 MPa.